Going Mobile: Guiding the Development of Safer and More Effective Mobile Access in Healthcare. (September 2017) - Lazzara, Elizabeth H.; Baker, Anthony L.; Abts, Natalie; Nathan-Roberts, Dan; Ranton, Justin; Fouquet, Sarah; Chaparro, Barbara
Smartphones and tablets continue to be weaved into our everyday lives. The proliferation of these technologies has also led to rapid growth in the number of medical technologies that are available. In particular, medical software offers a large variety of benefits, with specific applications serving as communication platforms, information references, health record databases, and much more. It is clear that medical software has myriad benefits, but it also presents many challenges, such as reliability, usability, and regulatory oversight. Thus, the objective of this discussion panel is to assemble professionals in the fields of healthcare, usability, and human-system integration to address the question: How can the sciences of human factors and medicine work together to influence the design and implementation of safe, effective mobile medical software?